Assessment Model in Education: Integration of Islamic Values in the Formation of Karamah Insaniah - Mohd Aderi Che Noh; Fadzila binti Rahman; Nurul Hidayah binti Razali; Anisah Triyuliasari (Yayasan Letiges Konsultan Sosial, 2025)
This study examines the educational assessment model that integrates Islamic values ​​in the formation of karamah insaniah in Malaysia. Malaysia has integrated Islamic values ​​in formal and non-formal education through the Malaysian Education Development Plan (RPPM) 2013-2025. This study uses a qualitative descriptive-analytical approach through a literature study by reviewing various relevant literature from academic sources, journals, articles, and books. Data analysis was carried out by reading, comparing, and identifying patterns and findings that emerged from the literature reviewed. Relevant data will be categorized into interrelated themes. Then the synthesis and interpretation of data to produce substantial research conclusions and findings. The results of the study indicate that the concept of karamah insaniah is a unification of the principles of the pillars of the state with the philosophy of national education that emphasizes the assessment of students' intelligence holistically based on the level of knowledge, skills, good deeds, and noble morals. The development of an assessment framework in education is based on three dimensions, namely the dimensions of faith, sharia, and morals. A well-designed assessment model can encourage the improvement of student character and create a more holistic educational environment by paying attention to spiritual and moral aspects along with academic achievement. This research contributes to the advancement of science, especially in the field of Islamic education in forming human character.